(untitled) (Journal of Science and Technology, 2016)
This study was conducted to assess the variation in performance of four arbuscular mycorrhizal fungi (Glomus clarum, Glomus etunicatum, Glomus intraradices, and Gigaspora rosea) with and without Rhizobium inoculation in promoting growth and nutrient (N and P) uptake inGliricidia sepium. Gliricidia seedlings were grown in sterilised (autoclaved) vermiculite and sand mixture in 2:1 (v:v). Each week, plants received 50 cm3 of nutrient solution (with N and P additions) according to the treatments. The experimental design was a 4x2 factorial arranged in a randomised complete block design. Seedlings were harvested after 12 weeks. Dry weights of plant parts, nodulation, arbuscular mycorrhizal fungal colonization, nitrogen and phosphorus concentration and content were determined. AM fungi differed in their effectiveness in enhancing growth of Gliricidia sepium. Glomus clarum was most efficient and produced statistically higher total plant dry weight than other mycorrhizal fungi. Dual inoculation with AM fungi and Rhizobium was effective in promoting host plant growth over Rhizobium- uninoculated mycorrhizal plants in terms of leaf area, shoot and root dry weights, total plant biomass and shoot-root ratio. Rhizobium-inoculated Glomus clarum treatment recorded significantly higher (approximately a third fold increase) total plant dry weight, than the similar treatments of Glomus etunicatum, Glomus intraradices and Gigaspora rosea. Shoot-root ratio was statistically greater with mycorrhizal plants inoculated with Rhizobium than the non-Rhizobium inoculated treatments due to improved mineral nutrition particularly nitrogen (through nitrogen fixation). Nodulation assessed by the number of nodules produced per plant was statistically similar between the Rhizobium- inoculated mycorrhizal treatments but significantly higher than the Rhizobium- inoculated non-mycorrhizal comparison treatment. Plants inoculated with Glomus clarum and Glomus intraradices significantly achieved higher root colonization than Glomus etunicatum and Gigaspora rosea. Rhizobium inoculation reduced root colonization with all the Glomus species except Gigaspora rosea. A highly significant (P<0.001) interaction between mycorrhiza and Rhizobium was observed for mycorrhiza root colonization. Rhizobium- inoculated treatments recorded significantly higher N concentration and content over non-Rhizobium mycorrhizal plants supplied with combined nitrogen. Inoculation with Glomus clarum significantly increased P concentration and content in all plant parts. Gigaspora rosea was least effective in promoting phosphorus uptake. Arbuscular mycorrhiza fungi infection was positively correlated with P concentration (%P) (r=0.74, P<0.01), and P content (mgP) (r=0.52, P<0.01). The study has shown the importance of some AM fungi for legume tree growth and nutrition and therefore in nutrient deficient soils, effective mycorrhizal fungus and Rhizobium could be used to promote growth and nitrogen fixation in N2-fixing tree seedlings.